Comprehending Columbine - Larkin, Ralph W. (Temple University Press, 2007)
On April 20, 1999, two Colorado teenagers went on a shooting rampage at Columbine High School. That day, Eric Harris and Dylan Klebold killed twelve fellow students and a teacher, as well as wounding twenty-four other people, before they killed themselves. Although there have been other books written about the tragedy, this is the first serious, impartial investigation into the cultural, environmental, and psychological causes of the massacre.Based on first-hand interviews and a thorough reading of the relevant literature, Ralph Larkin examines the numerous factors that led the two young men to plan and carry out their deed. Rather than simply looking at Columbine as a crucible for all school violence, Larkin places the tragedy in its proper context, and in doing so, examines its causes and meaning.
Description based on print version record.
KU Select 2016 Backlist Collection
Keywords: Social Science; Education / Educational Policy & Reform / School Safety; Social sciences; Electronic books